Formy uczestnictwa świeckich w życiu Kościoła. Refleksja na podstawie adhortacji apostolskiej Christifideles laici - Rutynowski, Mateusz (Społeczeństwo, 2022)
In 2018, it is thirty years since the publication of the apostolic exhortation Christifideles laici. On the basis of this exhortation and the Council documents, the question of who the lay person is in the sense of these documents and what are the forms of secular involvement in the life of the Church are presented. The secular person plays an important role in the Church because he has the task of evangelizing the environment in which he lives. The associations of the laity are an image of the community of the Church, which together seeks to build the Kingdom of God on earth.